The influence of market orientation and managerial capability on marketing performance with market market innovation as a mediating variable - Wesondra, Qory; Sari, Astri Yuza (Universitas Negeri Padang, 2024)
The aim of this research is to analyze the influence of market orientation, managerial capability, and market innovation on the marketing performance of small and medium-sized enterprises (SMEs) in the city of Padang. The population of this study comprises all owners of small and medium-sized enterprises in Padang. The sample size for this research was determined to be 94 samples using the Slovin formula. The data analysis technique employed is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The findings of this study indicate that (1) There is a significant influence of market orientation on marketing performance. (2) There is a significant influence of managerial capability on marketing performance. (3) There is no significant influence of market orientation on market innovation. (4) There is a significant influence of managerial capability on market innovation. (5) There is a significant influence of market innovation on marketing performance. (6) The market innovation variable cannot mediate the relationship between market orientation and marketing performance. (7) There is an indirect and significant influence of managerial capability on marketing performance through market innovation..